2015
DOI: 10.1007/s00436-015-4736-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contamination with Toxocara eggs and seroprevalence of toxocariasis in children of northeastern Poland

Abstract: Toxocariasis is a worldwide distributed zoonotic disease. Soil contaminated with Toxocara eggs appears to be the main source of infection for humans. The aim of our study was to estimate the environmental contamination with Toxocara eggs in public areas in northeastern Poland followed by the assessment of seroprevalence of toxocariasis in the children's population inhabiting the areas. A total of 168 soil samples were collected in June and September from public areas, and 28 from patients' residences. They wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
6
11
1
1
Order By: Relevance
“…Toxocara contamination prevalence varied over the course of the year, infection rate may vary depending on the season. 18,19 In this study the prevalence of Toxocara eggs detection in soil carried with seasons with higher prevalence in spring (37.2%), autumn (32.6%), In agreement with Some researchers who noticed that the presence of Toxocara eggs in sandpits located in Japan public parks, reporting a higher prevalence of eggs recovering during the autumn, spring and early summer. 20 In addition to in other countries, the highest egg prevalence have detected in these seasons 21,22 ) which is may be connected with the reproductive period of the definitive hosts in these seasons.…”
Section: Discussionsupporting
confidence: 90%
“…Toxocara contamination prevalence varied over the course of the year, infection rate may vary depending on the season. 18,19 In this study the prevalence of Toxocara eggs detection in soil carried with seasons with higher prevalence in spring (37.2%), autumn (32.6%), In agreement with Some researchers who noticed that the presence of Toxocara eggs in sandpits located in Japan public parks, reporting a higher prevalence of eggs recovering during the autumn, spring and early summer. 20 In addition to in other countries, the highest egg prevalence have detected in these seasons 21,22 ) which is may be connected with the reproductive period of the definitive hosts in these seasons.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the number of Toxocara eggs per sandpit sample was elevated from December to June, and highest numbers of infective Toxocara eggs were again found in January and February. Higher percentages of Toxocara contamination of playgrounds and public parks in winter and spring than in summer and autumn were also reported in other studies from Europe [23, 26], demonstrating a general pattern underlying this observation. Survival and development of Toxocara eggs depend on temperature, humidity and sunshine exposure [27, 28].…”
Section: Resultssupporting
confidence: 85%
“…Such range is comparable to current contamination rates found in Belgium and Poland [22, 23]. By contrast, Horn et al [12], who used a similar egg detection method, found 55.8% of Hanoverian playgrounds to be contaminated with Toxocara eggs in August 1985.…”
Section: Resultssupporting
confidence: 75%
“…The WB-confirmed Toxocara spp. seroprevalence in children was higher than a similarly confirmed estimate from children from Poland (4.2%, p < 0.001) [ 49 ]. Toxocara spp.…”
Section: Discussionmentioning
confidence: 88%